General Election Glorious Without Lies - Benito Asdhie Kodiyat (International Journal Reglement & Society (IJRS), 2022)
The problem to create a noble election, it is necessary to improve the electoral system comprehensively, the focus of the problems in this study will discuss about strengthening the role of election supervisory bodies in law enforcement, the roles that must be maximal and criteria in achieving elections of integrity, and involving the role of the State Administrative Chamber of the Supreme Court. The research method that is called juridical normative. The results showed that strengthening the function of the election supervisory agency in the enforcement of electoral law, then one of the leaders of the election supervisory body collectively collegial must be one of the public prosecution teams in the court so that it can control the enforcement of election law to the fullest and its role does not stop at the plenary. integrated law enforcement. For convicted of electoral crimes in addition to prison / confinement then his political rights are revoked. The special team consists of the legal field of the Election Commission and the Court in charge of arranging the regulations so that the election commission regulations are not prone to judicial review